FINANCIAL SERVICES AUTHORITY IN CONSUMER AND PUBLIC PROTECTION ON ONLINE LOAN BASED ON FINANCIAL SERVICES AUTHORITY REGULATION (POJK) NUMBER 22 OF 2023 - Yuli Antono, Vydo; Saputra, Arikha (fakultas hukum universitas PGRI Semarang, 2025)
This research employs a normative juridical method, using a statutory approach and literature review related to consumer protection in the online lending industry. The analysis focuses on the Financial Services Authority Regulation (POJK) Number 22/POJK.01/2023 as the legal basis for consumer protection in the financial services sector, particularly in technology-based lending services. The findings reveal that POJK Number 22/POJK.01/2023 provides a stronger legal foundation for consumer protection by emphasizing the obligations of financial service providers to deliver transparent information, uphold fair treatment principles, and offer responsive complaint handling mechanisms. Additionally, the OJK holds the authority to supervise and take action against violations committed by online lending providers.In conclusion, the Financial Services Authority plays a strategic role in protecting consumers and the public in the online lending sector through the implementation and supervision of POJK Number 22. This regulation serves as a crucial instrument to encourage ethical, transparent, and responsible business practices among service providers, while also ensuring a sense of security for the public in accessing digital financial services